TINGKAT PRODUKTIVITAS PETANI PADI DI DESA BOLUDAWA KECAMATAN SUWAWA KABUPATEN BONE BOLANGO - Imbran, Harijono; Maksum, Fatma (Universitas Muhammadiyah Gorontalo, 2024)
Farmer productivity is an element that is always a target in every farming business, this study aims to find out how the productivity of rice farmers in Boludawa Village, Suwawa District, Bone Bolango Regency. This study uses a descriptive quantitative approach. The research instrument used a questionnaire distributed to 40 respondents. The analytical method used in this research is using multiple regression analysis equipment, which involves three variables, namely X1 (fertilizer costs), X2 (labor costs) and Y (farmer productivity). This research concludes that there is a significant effect between the production factors X1, and X2 on the productivity of rice farmers (Y) in Boludawa Village, Suwawa District. Significance was shown by the results of the analysis and obtained the multiple linear regression equation Y = 364,064,324 + 0,764X1 + 2,001X2. The productivity of rice farmers in Boludawa Village, Suwawa District is influenced by the magnitude of the R squre value of 0.628 or 62.8 percent of rice farmers' productivity is influenced by the amount of fertilizer costs and labor costs used.